OPTIMASI VARIASI VOLTASE DAN WAKTU TERHADAP KUALITAS PITA DNA ESCHERICHIA COLI PADA PROSES ELEKTROFORESIS GEL AGAROSA - nur amani putri, afifah; Iin Nur Indra, Asep; Merdekawati, Fusvita; Khoirul Abror, Yogi (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Escherichia coli is one of the causes of foodborne illness. Conventional PCR is a PCR method that is carried out qualitatively followed by visualization on agar electrophoresis. Agarose gel electrophoresis is a technique that is often used in various fields of science to separate a mixture of DNA on agarose substrate. This method is used to perform qualitative analysis of DNA samples. In electrophoresis, there are factors that affect the movement of DNA molecules, one of which is voltage. In addition, the length of time of the electrophoresis process can also affect the effectiveness of the results and the rate of migration. When the electrophoresis process time is short, large DNA fragments still tend to stick. Purpose: Therefore, it is necessary to balance the voltage and time given to get good DNA banding results. Methods: The research unit that will be used is the result of amplification of Escherichia coli 16SrRNA gene DNA measuring 584 bp. The electrophoresis process was carried out with voltage variations of 50, 100, 150 volts and time variations of 30, 45, 60 minutes. Observation of electrophoresis results that have formed DNA bands will be measured the area of DNA bands using ImageJ application. Conclusion: Based on the results of the study concluded that: The optimum voltage in the electrophoresis process in obtaining good E.coli DNA bands is at a voltage of 150 volts. The optimum time in the electrophoresis process in obtaining good E.coli DNA bands is for 30 minutes.